Literary between formalism and Deconstruction - BENSSOKHRI, ZOUBEYR (Milev Journal of Research and Studies, 2022)
Literarity has been considered as an important feature within the literary criticism during the twentieth century, particularly with the adoption of the structural linguistic framework which viewed it as an end in itself while criticising the litrary texts. However, with the advent of the philosophy of deconstruction with the French philosopher Jacques Derrida in the 1970s, and the emergence of new concepts for text and literature, there appeared some cultural and semiotic approaches which go beyond the traditional concepts for literarity. The latter has no longer a direct relationship with the self, but has become an experience for the meaning before reaching the concept, where all the taxonomic features of the text disappear, and literature has come to be –in the absence of the centre- part of the culture rather than representing an aestheticcentre as it was.